Testing Stochastic Convergence among Mexican States: A Polynomial Regression Analysis - German-Soto, Vicente; Salazar Garza, Natalia (Journal of Reviews on Global Economics, 2016)
Another look on the economic convergence among Mexican states is offered examining whether they are approaching along 1940-2010. Methodology is based on polynomial regressions, a method that determines whether predictions can be significantly improved by increasing the complexity of the fitted straight-line model. Estimates from a set of polynomial terms are a theoretical approximation to income differentials, so it constitutes an adequate frame to analyze if different initial conditions tend to diminish in the long-run. We calibrate for each economy the polynomial equation of best adjustment supported in information criteria and a strategy of backward iterative elimination. Empirical results are according with the stochastic convergence, but in a relationship where it changed after trade opening, poorer states are diverging and richer states are converging. A focalized regional policy is necessary with the aim to correct the biases produced in a context where some regions are lagging while others more are advancing.